Baseline characteristics of systemic sclerosis patients with restrictive lung disease in a multi‐center US‐based longitudinal registry. (28th November 2021) - Castelino, Flavia V.; VanBuren, John M.; Startup, Emily; Assassi, Shervin; Bernstein, Elana J.; Chung, Lorinda; Correia, Chase; Evnin, Luke B.; Frech, Tracy M.; Gordon, Jessica K.; Hant, Faye N.; Hummers, Laura K.; et al.
Abstract: Aim: Interstitial lung disease (ILD) is the leading cause of disease‐related death in systemic sclerosis (SSc). Here, we assess baseline characteristics of SSc subjects with and without restrictive lung disease (RLD) in a multi‐center, US‐based registry. Methods: SSc patients within 5 years of disease onset were enrolled in the Collaborative National Quality and Efficacy Registry (CONQUER), a multi‐center US‐based registry of SSc study participants (age ≥ 18 years) enrolled at 13 expert centers. All subjects met 2013 American College of Rheumatology / European League Against Rheumatism criteria. Subjects with a pulmonary function test (PFT) at baseline before April 1, 2020 were included. High‐resolution computed tomography scan of the chest was not available to characterize ILD for all subjects. RLD was defined as forced vital capacity (FVC) <80% or total lung capacity (TLC) <80% predicted. Results: There were 160 (45%) SSc subjects characterized as having RLD. There was no significant difference in age, gender or disease duration. RLD subjects had a mean disease duration from date of first non‐Raynaud's symptom of 2.6 years and a mean FVC% predicted of 67% at baseline. In multivariable analysis, non‐White race, higher physician global health assessment and modified Medical Research Council (mMRC) dyspnea scores, were independently associated with RLD. In the subgroup of RLD subjects with ILD, ILD had a negative correlation with RNA polymerase III antibody. Conclusion: CONQUER is the largest, multi‐center, prospective cohort of early SSc patients in the US. Non‐White race was independently associated with RLD. In addition, 45% of CONQUER subjects already had RLD, highlighting the importance of screening for SSc‐ILD at initial diagnosis.